2017
DOI: 10.1002/chem.201703812
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Control of MOF Crystal Orientation and Alignment

Abstract: Most metal-organic frameworks (MOFs) possess anisotropic properties, the full exploitation of which necessitates a general strategy for the controllable orientation of such MOF crystals. Current methods largely rely upon layer-by-layer MOF epitaxy or tuning of MOF crystal growth on appropriate substrates, yielding MOFs with fixed crystal orientations. Here, the dynamic magnetic alignment of different MOF crystals (NH -MIL-53(Al) and NU-1000) is shown. The MOFs were magnetized by electrostatic adsorption of iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…111 Due to its attractive properties such as having a high Brauner-Emmett-Teller (BET) surface area (2320 m 2 g À1 ) and pore volume (1.4 cm 3 g À1 ), good thermal stability, fluorescence properties and the suitability of the structure for metalation or other types of functionalization, NU-1000 has drawn attention since its first synthesis. As a result, the chemical and structural properties of NU-1000 have been deeply studied experimentally and computationally; by exploring its synthesis conditions, [112][113][114][115][116][117] structural stability, 118,119 proton topology and surface chemistry, 120-123 and designing organic linkers for its better crystallinity. 124…”
Section: Synthesis Of Pyrene-based Mofsmentioning
confidence: 99%
“…111 Due to its attractive properties such as having a high Brauner-Emmett-Teller (BET) surface area (2320 m 2 g À1 ) and pore volume (1.4 cm 3 g À1 ), good thermal stability, fluorescence properties and the suitability of the structure for metalation or other types of functionalization, NU-1000 has drawn attention since its first synthesis. As a result, the chemical and structural properties of NU-1000 have been deeply studied experimentally and computationally; by exploring its synthesis conditions, [112][113][114][115][116][117] structural stability, 118,119 proton topology and surface chemistry, 120-123 and designing organic linkers for its better crystallinity. 124…”
Section: Synthesis Of Pyrene-based Mofsmentioning
confidence: 99%
“…22 We have previously shown that magnetized NU-1000 could be dynamically aligned via magnetic fields. 22 However, the use of electric fields for MOF alignment would significantly widen the scope for device integration as it is simpler and more practical to implement for many applications. E-fields also have a greater dynamic range of field strengths and are easier to localize, avoiding cross-talk or interference within devices.…”
mentioning
confidence: 98%
“…We previously showed that magnetically aligned NU-1000/Sylgard 184 composites exhibited a fluoresence response which was dependent upon the angle of linearly polarized excitation. 22 This angular dependence arises from the lattice anisotropy of NU-1000, as the pyrene-based TBAPy ligands are oriented along the C-axis (Figure 1) and hence display anisotropic absorbance of linearly polarized excitation. Drawing upon this, we carried out fluorescence response studies on NU-1000Si suspensions.…”
mentioning
confidence: 99%
“…Nevertheless, other strategies involving the in situ formation or the post-synthetic chemical modification of microporous materials have also been proven to be successful. In this sense, the use of different external stimuli, such as electromagnetic fields 94 or laser guided patterning 95 could be considered useful tools to achieve precise spatial positioning.…”
Section: Discussionmentioning
confidence: 99%